Gender and Age Influence in Pre-Competitive and Post-Competitive Anxiety in Young Tennis Players - Rafael Martínez-Gallego (Sustainability, 2022)
To study the influence of age and gender on pre-competitive and post-competitive anxiety and self-confidence in young tennis players. A total of 42 U’12 to U’18 category tennis players, 12 females and 30 males, participated in this cross-sectional study. The players had a mean age of 13.74 (2.07) years old and a national competitive experience of 4.00 (2.14) years. The pre-competitive anxiety of the participants was assessed using the Competitive State Anxiety Inventory–2R (CSAI-2R) and the State Trait Anxiety Inventory (STAI-E) before and after an official tournament’s match. Results showed that younger players showed lower trait anxiety (r = 0.333; p < 0.05), lower pre-match state anxiety (r = 0.501; p < 0.01) and lower pre-match somatic anxiety (r = 0.313; p < 0.05). Furthermore, girls exhibited higher values of state anxiety (r = 0.445; p < 0.01) and somatic anxiety (r = 0.440; p < 0.01) than boys before the match. However, differences were not observed in the trait anxiety measured by STAI-E (r = 0.203; p = 0.213), cognitive anxiety (r = 0.140; p = 0.363), and self-confidence measured by the CSAI questionnaire (r = 0.150; p = 0.333), before the match. Therefore, coaches and sport psychologists should implement adequate on- and off-court individualized interventions to manage anxiety, specifically in girls and players over 14 years old. Although anxiety levels were similar to those before the COVID-19 pandemic, due to the influence of the pandemic on mental health, results might be taken with caution.